INFLUENCE LAPROLAT LT – 803 AND OLIGOETHER L - 501 - 2 - 100 ON IMMUNОLOGICAL REACTIVITY IN SUBACUTE EXPERIMENT - Багмут І. Ю. (World of Medicine and Biology, 2015)
This work is a piece of research KhNMU "Studding mechanisms biological action polyethers simple have problems health circumflex media", state registration number 0110U001812. Introduction. Prolonged exposure to physical, chemical, biological and social factors leading to sensitization of the human body and chronic activation of allopathological disease [4]. In this regard, there is a large number of tasks on the influence of environmental factors on the state of specific and nonspecific resistance of the organism immunobiological person. The driving forces of environmental protection is to solve actual problems for the study of the causes that contributed to the disruption of the ecological balance in the regions of eastern and south-eastern Ukraine, which can be attributed Kharkov, Zaporozhye, Dnepropetrovsk regions and industrial Donbass. Industrial enterprises pose a serious threat to the ecology [5,11]. Deserves special attention the view that the main causes that contribute to the formation of pathologies of the population, is the natural and man-made ecological factors [12,13]. Due to the progressive development of human activities on the environment, there is an infringement of ecological systems, which leads to a change in adaptive processes in the body, the development of immune deficiency and reduce the overall resistance of the organism. According to the researchers anthropogenic effects on the biosphere has the chemical industry [5]. Justification of the molecular mechanisms of formation of violations under the influence of chemical compounds and characteristics of their influence on the human body, its immunobiological resistance is one of the tasks of research aimed at improving the non-specific reactivity and improving the health of the population. [1, 2, 3, 5, 13]. Large volumes and the widespread introduction into production and life Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 raises important and urgent problems of modern rapid assessment of biological activity and the risk of new groups and compounds chemical series, and their impact on the state of immunobiological reactivity [7]. Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 are new groups of chemicals organic synthesis industry - oligoethers, which are widely used to produce foams, thermoplastic, epoxy resins, lacquers, enamels, polyurethanes, plastics, synthetic leather, etc. Interest in this class of compounds due to the large volume of production, a wide range of products and their significant exposure to the population [10,14]. All this proves the relevance of the study of the molecular mechanisms of the formation of structural and metabolic disturbances of the immune homeostasis by the action of a living organism chemicals technical name Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 and determine its potential danger to human health and environment. In this regard, the study of the influence of oligoether on cellular and humoral immunity and justification forecast potential danger to their person is an actual problem, the solution of which is aimed at increasing resistance and improving the health of the population in a state of crisis of the biosphere. The aim of the present work was experimental and theoretical study of the molecular mechanisms of formation of disturbances of cellular and humoral immunity in effect on the body Laprolat Lt - 803 and oligoether L - 501 - 2 - 100, rendering the anthropogenic impact. To achieve the goal were as follows: To investigate the cellular and humoral immunity in experimental animals exposed to oligoethers such as Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 under subacute experiment on mice (СВАхС57ВL)F1, BALB/C and white Wistar rats in subacute experiment; identify possible inhibition of cellular and humoral immunity, the underlying violations immunobiological reactivity of warm-blooded animals - mice (СВАхС57ВL)F1, BALB/C and white Wistar rats. Materials and methods. We used chemicals with regulated physicochemical characteristics Laprolat - 803 and oligoether L - 501 - 2 - 100. In the study of immunobiological reactivity of animals stuck "Guidelines evaluation immunobiological actions of chemicals" (Russian Ministry of Health, 1998). Studies of the effect of the substance on cellular and humoral immunity were performed on adult mice hybrid line (СВАхС57ВL)F1, BALB/C weighing 21-25g and Wistar rats weighing 180-200 g., Which were kept on a standard diet of the vivarium. Experimental setup was in accordance with the "General principles of ethical conduct experiments on animals" (Ukraine 2001), Which comply with the provisions of the European Convention "On protection of vertebrate animals used for experimental and other scientific purposes" (Strasbourg, 1986). Animal test group orally by a metal probe daily for 45 days, an aqueous solution containing glycols. Calculate the required dose of the substance was performed based on data on the characteristics of their toxicity. The optimum dose for the study of biochemical processes, status indicators in mice is the dose of LD50. To examine the state of immune system was used 1/10 and 1/100 and 1/1000 LD50. Control group animals were administered a corresponding quantity of drinking water. After completion of laboratory animals toxification cellular and humoral immunity was studied by immunofluorescence method [8,9,15]. To assess the cellular component of the immune system determines the total population of T lymphocytes (CD3 +) subpopulation of T-lymphocytes: T-helper cells (CD4+) T-suppressor (CD8+) and β-lymphocytes (CD19+) in serum. Mediators of the immune system - immunological reactions adjuvants, interleukins - (IL-1β, IL-2, IL-4, IL-6) and tumor necrosis factor - α (TNF-α) were determined in serum by enzyme immunoassay and diagnostic use test systems company "Protein contour" (St. Petersburg, Russia). Study of regulatory cytokines (IL-8) was carried out using the test system of the company «Diaclone» (France). Humoral immunity of mice was evaluated on the content of immunoglobulin A, M, G, D, E in serum by enzyme immunoassay according to the instructions on the attached enzyme immunoassay analyzer. Results of the study are statistically processed using Student’s t test, Fisher. Results and discussion. Study of the effect Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 on cellular and humoral immunity is found that xenobiotic 1/10 LD50 in subacute effects on experimental day 45 led to a reduction in serum content of T- and B-lymphocytes immunoglobulins and cytokines studied. In 1/100 LD50 dose of xenobiotics in the least influenced the parameters of cellular and humoral immunity. Substance at this dose did not affect the content of serum immunoglobulins: IgD and IgE concentration was not disrupted IL-6 and IL-8 in comparison to the control group observation. Studies have shown inhibition of cellular and humoral immune system in 1/10 and 1/100 LD50. Thus, it was found that reducing the total number of xenobiotics T-lymphocytes and their subpopulations - T-helpers and T-suppressors in serum. From this it can be expected reduction products helper T regulatory large number of mediators of the immune system - TNF-α, IL-1β, IL-2, IL-4, IL-6, IL-8, which are activators of B-lymphocytes and mast hematopoietic cells, thymocytes, neutrophils, monocytes, macrophages, fibroblasts, splenocytes. We believe that the observed experimentally exposed Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 reduction of IL-1β, may slow down the processes of differentiation and tissue regeneration, the production of prostaglandins, alpha-Tumor Necrosis Factor (TNF-α) macrophages, monocytes, histiocytes, immunoglobulin synthesis by B-lymphocytes. This inhibition of cell immunity was associated with inhibition of serum levels of IL-2, IL-4, IL-6, which play an important role in the proliferation and differentiation of T and B-lymphocytes, antibody synthesis switching from one class of immunoglobulins another. Inhibition of cytokine ability of mononuclear cells was confirmed by a decrease in the concentration of IL-1β, TNF-α, IL-2, IL-4, IL-6, IL-8, indicating that the inhibition of cellular immunity and processes associated with intercellular mediator interactions, which are aimed at ensuring homeostatic function of the immune system. Considering reduction of IL-4 in the serum inhibition of the process can be accompanied by antigenic stimulation of T lymphocytes, macrophages, mast cells, basophils, B lymphocytes, stromal cells, hematopoietic progenitors, and others. It is known that IL-4 induces the differentiation (CD4) T lymphocytes into helper T cells of the second type (TH2), and suppresses the development of T helper type first (TH1) and stimulates proliferation and differentiation of B-lymphocytes, promotes the production of IgE by B lymphocytes and mediator effects on various other cell types, including macrophages and granulocytes [15]. Studies have shown that under the influence of 1/10 LD50 more intensely inhibited both humoral and cell-mediated immune system, than compared to 1/100 LD50. It should be noted that the study of xenobiotics in doses suppressed the proliferation and differentiation of B-lymphocytes. These judgments were confirmed by a decrease in the level of serum CD19. Analysis of the results shows that the addition of macrophages, basophils, T- and B-lymphocytes, mast cells undergo antigenic inhibiting monocytes, fibroblasts, endothelial cells, hepatocytes, neurocytes, astrocytes, which are producers of IL-6. Reduction of IL-6 in the serum of experimental animals may be subject to a violation of differentiation of hematopoietic cells - precursors. Due to the fact that this is a cytokine inducer these processes, it stimulates the maturation of thymocytes, spleen cells, megakaryocytes and production of platelets, promotes the growth and maturation of T and B lymphocytes, T-lymphocyte transformation in cytotoxic T cells, enhances the production of acute phase proteins by hepatocytes and is an endogenous pyrogen. The studies also showed inhibition of IL-8 production under the influence of investigated xenobiotics 1/10 1/100 LD50. It should be noted that the produced mononuclear phagocytes (monocytes of peripheral blood macrophages of connective tissue liver, alveolar lung macrophages, free and fixed macrophages of the lymph nodes and spleen, macrophages Serous cavities macroglia CNS cells, osteoclasts inert tissue), IL-6, IL-8 can exert an activating effect on T-helper cells (CD4) cytotoxic T cells (CD8), B-lymphocytes. The observed inhibition of the production of these cytokines may be an important mechanism of inhibiting cellular and humoral immunity. Carrying out the effector function of immune reactions activated by cytokines (IL-6, IL-8, IL-4, IL-2), neutrophils and macrophages are highly phagocytic and bactericidal capacity are involved in the induction of humoral and cell immunity, stimulate the production of TNF-α and cytotoxic oxygen species that lead to the elimination and destruction of foreign cells in a tumor and the antibody-dependent cellular cytotoxicity. Intercellular interactions enable the mediator to judge that the test group of animals exposed Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 observed reduction of cytotoxic T lymphocytes (CD8) from which during the development of the cellular immune response are differentiated NK cells (large granular lymphocytes) and T-killer cells which can have a direct cytotoxic effect on the target foreign cells, their modified cells, including tumor and virus-infected cells [7,10,15]. On large granular lymphocytes expressed receptors for IL-2, which is possible through their stimulation. Reduced levels of IL-6, IL-8, TNF-α, IL-2 in the serum of the experimental animal can be an important pathogenic mechanism of breaking links inhibiting the functional activity of NK cells, killer T cells that have cytotoxic effects on cells - targets as by contact lysis or via factors secreted in the form of granules or substrates within these cells in idle state [15]. These cytotoxic cells are active producers of a particular protein perforin, which polymerizes on the target cells to form an transmembranes pore, through which the hyperhydration cells and DNA damage target cells and the cell itself. Studies show that Laprolat Lt - 803 and oligoether L - 501 - 2 – 100 in 1/10 and 1/100 LD50 can inhibit the cytotoxic activity of immune cells. Significant inhibition of the production of immune system mediators, including IL-6, which is a mitogen for T-lymphocytes, and reduction of the synthesis of IL-8, acting as an inducer of acute inflammatory response, adhesion properties stimulator of neutrophils and T-lymphocyte chemotaxis, as evidenced abuse cooperative the interaction of cellular and humoral immunity against the background of the formation of immune deficiency. Taking into account that IL-2, IL-4, IL-6 provide cellular component of the adaptive immune system [9], we have analyzed the functional activity of B-lymphocytes and the content of serum immunoglobulins. Results of studies found a significant decrease in the content of B-lymphocytes and immunoglobulins: IgG, IgM, IgA, IgD, IgE, which may be associated with functional activity by inhibiting β-lymphocytes plazmoblasts that are the main producers of antibodies [9,10,15]. Determination of antibody producing cells and immune functions primarily B lymphocytes revealed a significant decrease in the concentration of immunoglobulins - IgG, IgM, IgA and IgD to a lesser degree, and IgE, which are exposed to xenobiotics 1/100 LD50 levels were not different from controls. Thus, the results of research led to the following conclusions: 1. Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 in a subacute experiment with ingestion intragastrically 1/10 and 1/100 of LD50 inhibit the functional activity of the cellular component of the immune system by reducing the content of blood serum of experimental animals total population of T lymphocytes (CD3 +) subpopulations of T-lymphocytes - T-helper cells (CD4), T-suppressors (CD8) and В-lymphocytes (CD19). 2. Laprolat Lt - 803 and oligoether L - 501 - 2 - 100 on the background of inhibition of cell immunity in 1/10 and 1/100 LD50, able to inhibit the synthesis of regulatory cytokines and mediators induction of acute-phase reaction, which is associated with inhibition of antibody immune function cells and violation of cooperative interaction of cellular and humoral immunity. In all cases, xenobiotics in 1/1000 LD50 no effect on the immunological reactivity of the experimental animals. Prospects for further research To form the conceptual model of the molecular mechanisms of formation of disorders of cellular and humoral immunity in effect on the body Laprolat Lt - 803 and oligoether L - 501 - 2 - 100, further experimental and theoretical study of integrative systems evaluation and control of homeostatic functions of the body when exposed to the test chemical class.